Effect of Product Quality Brand Image Towards Purchasing Decision With Trust as an Intervening Variable - Riandi Jahja (Syntax Literate, 2022)
This paper proposes a research to analyze empirical effect of the quality of product and brand image towards purchasing decision with trust as an intervening variable. This recearch is conducted in Jakarta involving 160 users of Lazada, this study uses purposive sampling, as the sampling method.The data is analyzed using smartPLS, SEM based analysis tool. The result shows that partially product quality has no significant effect towards purchasing decision and so does trust, however brand image has significant effect towards purchasing decision. Subsequently, product quality affects trust, brand image doesn’t. Both of product quality and brand image has no significant impact towards purchasing decision though trust. This happened because most online shoppers are stimulated by the brand image not trust. Brand identity, brand ambassadors, and engaging advertising are the advantages which Lazada lack of that competitors have. This study prmopts to put additional effort to convince consumers, in this case users of Lazada, through defining image of the brand by utilizing fanbase and entertainment approach to marketing.